Who Creates New Firms When Local Opportunities Arise? - Bernstein, Shai (IMF Working Papers; Working Paper ;, 2018)
New firm formation is a critical driver of job creation, and an important contributor to the responsiveness of the economy to aggregate shocks. In this paper we examine the characteristics of the individuals who become entrepreneurs when local opportunities arise due to an increase in local demand. We identify local demand shocks by linking fluctuations in global commodity prices to municipality level agricultural endowments in Brazil. We find that the firm creation response is almost entirely driven by young and skilled individuals, as measured by their level of experience, education, and past occupations involving creativity, problem-solving and managerial roles. In contrast, we find no such response within the same municipalities among skilled, yet older individuals, highlighting the importance of lifecycle considerations. These responsive individuals are younger and more skilled than the average entrepreneur in the population. The entrepreneurial response of young individuals is larger in municipalities with better access to finance, and in municipalities with more skilled human capital. These results highlight how the characteristics of the local population can have a significant impact on the entrepreneurial responsiveness of the economy.